COVID-19 in Russia's Arctic - Silinsky, Leah (DEU, 2024)
This article lays out the broad dimensions of Russia’s response to the COVID-19 pandemic and then shows how these policies affected developments in the Arctic. The Kremlin initially denied that the disease would be a problem and then, when such denials were no longer tenable, has sought to minimize reports of its impact through pressure on doctors and journalists. Several doctors have died in mysterious circumstances. The Arctic has not been immune from the disease, with outbreaks coming from migrant workers building new energy infrastructure.